Countering Criminal Acts Of Terrorism By The Indonesian National Army According To Law Number 34 Of 2004 Concerning The Indonesian National Army - Anbastian Daniel Sinaga; Parlin Dony Sipayung; Desy Kartika C. Sitepu (Academic Solution Publisher, 2024)
Terrorism is an Extraordinary Crime that is transboundary in nature, involves international networks in an organized manner both individually and in groups, and has a major impact on the state and nation, where acts of terror arise in structural conflicts based on social, political and religious ideologies that give birth to an understanding of radicalism; in the context of counterterrorism, the involvement of the Indonesian National Armed Forces (TNI) has been regulated in Law Number 34 of 2004 concerning TNI, which underlies the role of TNI in Military Operations Other Than War (OMSP) to deal with the threat of terrorism as also stipulated in Article 43 I of the Terrorism Law, where its implementation is further regulated through a Presidential Regulation (Perpres); the efforts made by the TNI in maintaining the sovereignty of the Republic of Indonesia are oriented towards criminal law reform with a policy and value approach, while still emphasizing the principle of law enforcement, as stipulated in Law Number 5/2018 on the Eradication of the Criminal Acts of Terrorism and the plan to issue a Presidential Regulation governing the involvement of the TNI in combating terrorism; however, the obstacles faced by TNI and Polri in dealing with acts of terrorism include the lack of assertiveness of national leadership, the tendency of the government to be reactive with the pattern of handling “fire fighting units”, as well as the lack of preventive policies in anticipating acts of terrorism before they occur, causing the government to often miss, coupled with the lack of public understanding of TNI's involvement in handling terrorism, which is actually mandated by the TNI Law, thus raising suspicion of TNI's role in eradicating acts of terrorism.